Conversations on Peirce : reals and ideals - Anderson, Douglas R. (American philosophy., 2012)
Peirce on Berkeley's nominalistic Platonism / Doug Anderson, Peter Groff -- Who's a pragmatist: Royce, Dewey, and Peirce at the turn of the century / Doug Anderson -- Two Peircean realisms: some comments on Margolis / Carl R. Hausman, Doug Anderson -- The degeneration of pragmatism: Peirce, Dewey, Rorty / Doug Anderson -- Peirce's dynamical object: realism as process philosophy / Carl R. Hausman -- Another radical empiricism: Peirce 1903 / Doug Anderson -- Peirce on interpretation / Carl R. Hausman -- Peirce and Pearson: the aims of inquiry / Doug Anderson, Michael J. Rovine -- The pragmatic importance of Peirce's religious writings ; Realism and idealism in Peirce's cosmogony ; Love of nature: the generality of Peircean concern ; Developmental theism: a Peircean response to fundamentalism / Doug Anderson -- Peirce's coefficient of the science of the method: an early form of the correlation coefficient / Michael J. Rovine, Doug Anderson.